Comparative studies on N'Dama and zebu cattle following repeated infections with Trypanosoma congolense - Dwinger, R.H.; Clifford, D.J.; Agyemang, K.; Gettinby, George; Grieve, A.S.; Kora, S.; Bojang, M.A. (Elsevier, 1992)
This study is designed to examine the nature of trypanotolerance, in particular to compare the clinical parameters of infected N'Dama with those of infected Zebu cattle and the variability and repeatability within the N'Dama breed of various disease parameters. Twenty N'Dama and light Zebu cattle were inoculated intradermally with bloodstream forms of a cloned strain of Trypanosoma congolense originating from East Africa. All inoculated cattle became parasitaemic. Zebus showed consistently higher levels of parasitaemia and lower PCV percentages than did N'Damas. Three of the eight Zebus required treatment. The variation in PCV values was large between individuals during the early stages of the disease and diminished as infection continued. After trypanocidal drug treatment and a recovery period of 14 months, the same animals were inoculated intradermally with T. congolense blood-stream forms isolated and cloned in the Gambia. Differences in susceptibility to the ensuing disease were apparent when comparing N'Dama and Zebu cattle. Five Zebu cattle needed trypanocidal drug treatment, while none of the N'Damas needed during intervention.